(3QSGdI TQjaI aj HYV eSGFd GdQVGYs - (3GdcQcj, GdYGedj, CHh GdMSf, GdeMbb GdKGfj, Ydj Hf GdMSjf Hf YHO GdYGdj, J (B940 (3g`s ((3eMeO Hf aQL Gddg Hf ESeGYjd Hf Ydj Gdfaj GdJHQjRj GdaQhjs)
(3ChdgG (B:s
(3GdMeO ddg (B... (3GYde habc Gddg Gfg bO GTJgQ Ydi CdSfI GdWdHI aj gPG GdYUQ JMQje GdeQCI Ydi HYdgG HEQVGY HYV ef SfPcQg hdG fYQa dge aj Pdc CUdG jQLYhf Edjg ef cJGH Gh SfI Gh ELeGY(B...s
(3BNQgG (B:s
... (3gfG HGdeYfi GdCNU hdjS HKGHJ Hd jeJfY GdJdGRe CUdG aEf KHhJ HfhI TNU jbJVj KHhJ GdENhI dGhdGOg dGKHhJ GdCNhI dCNhI ChdGOg hPdc ZjQ ebJV ddJMQje HhLg ef GdhLhg hGddg CYdes
(3bhHdJ Ydi fSNI ebGHdI Ydi fSNI HNW GdeDdas
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe , ddRQcdj (B4/281s
(3GdPQjYI (B11 - 138 ( 1179)s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3abg GdePGgH GdCNQis